PREVALENCE OF HYPERTENSION IN NEWLY DIAGNOSED TYPE 2 DIABETIC PATIENTS PRESENTING TO OUTPATIENT DEPARTMENT OF PROVINCIAL HEADQUARTER HOSPITAL, GILGIT (The Research of Medical Science Review, 2025)
Background: The rising prevalence of diabetes in Pakistan, coupled with its association with hypertension, poses significant public health challenges. Objective: To determine the frequency of hypertension in newly diagnosed type 2 diabetic patients presenting to Out Patient Department. Methodology: A cross-sectional study was conducted at the Outpatient Department of Provincial Headquarter Hospital, Gilgit, over six months. A sample of 149 newly diagnosed type 2 diabetic patients (aged 30–60 years) was selected using non-probability consecutive sampling. Hypertension was defined as blood pressure ≥140/90 mmHg, and diabetes was confirmed via HbA1c levels >6.5%. Data on demographics, clinical parameters, and blood pressure were collected and analyzed using IBM-SPSS Version 23. Chi-square tests were employed to assess associations between hypertension and variables like age, gender, and residence. Results: Among the participants, 44.3% (n=66) had hypertension. The mean HbA1c was 7.8 ± 1.2%, indicating poor glycemic control, and the mean BMI was 28.5 ± 3.4 kg/m², suggesting overweight/obesity trends. Hypertension prevalence was significantly higher in older age groups (51–60 years, p=0.02), but no significant associations were found with gender (p=0.45) or residence (p=0.32).